1977
DOI: 10.1042/bj1620001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prostaglandin on substrate uptake and cell division in human diploid fibroblasts

Abstract: PG (prostaglandin) El inhibits the uptake of uridine, thymidine, 2-deoxy-D-glucose and L-isoleucine into human diploid WI38 fibroblasts. The inhibition occurs within seconds of the addition of the prostaglandin to the culture. PGE2, PGFlm and PGF2. behave similarly. Arachidonic acid and 8,11,14-eicosatrienoic acid also decrease uptake in the presence or absence of indomethacin. Other unsaturated fatty acids such as oleic acid, linoleic acid and linolenic acid are essentially inactive. Ricinoleic acid (the 9-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Much of the metabolism of arachidonic acid in cell populations is probably not basal but occurs in response to specific extracellular signals a t the cell surface. Earlier reports have shown that the state of proliferation and confluence of the fibroblast influences its response to the hormone agonist bradykinin (Taylor and Polgar, 1981;Whiteley and Needleman, 1984) and that the PGE2 released in turn causes a decrease in the proliferation of the fibroblast (Taylor and Polgar, 1977;Polgar and Taylor, 1977). Since the matrix-embedded cells are nonproliferative but still nonconf luent, examining whether the stimulated responses of these cells resemble those of confluent fibroblasts may aid in the interpretation of data obtained from cells grown on plastic.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the metabolism of arachidonic acid in cell populations is probably not basal but occurs in response to specific extracellular signals a t the cell surface. Earlier reports have shown that the state of proliferation and confluence of the fibroblast influences its response to the hormone agonist bradykinin (Taylor and Polgar, 1981;Whiteley and Needleman, 1984) and that the PGE2 released in turn causes a decrease in the proliferation of the fibroblast (Taylor and Polgar, 1977;Polgar and Taylor, 1977). Since the matrix-embedded cells are nonproliferative but still nonconf luent, examining whether the stimulated responses of these cells resemble those of confluent fibroblasts may aid in the interpretation of data obtained from cells grown on plastic.…”
Section: Discussionmentioning
confidence: 99%
“…At a concentration of 50 μM, Ricinoleic Acid suppressed the uptake of uridine into human diploid fibroblasts in culture (Polgar and Taylor 1977).…”
Section: Effect On Uridine Uptakementioning
confidence: 96%